2021
DOI: 10.1021/acsenergylett.1c00553
|View full text |Cite
|
Sign up to set email alerts
|

Energy vs Charge Transfer in Manganese-Doped Lead Halide Perovskites

Abstract: Mn-doped lead halide perovskites exhibit long-lived dopant luminescence and enhanced host excitonic quantum yield. The contention between energy and charge transfer in sensitizing dopant luminescence in Mn-doped perovskites is investigated by state-of-the-art DFT calculations on APbX 3 perovskites (X = Cl, Br, and I). We quantitatively simulate the electronic structure of Mn-doped perovskites in various charge and spin states, providing a structural/mechanistic analysis of Mn sensitizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…The photogenerated charge carriers in the Mn:CsPbCl 3 NCs have four elementary transfer routes: 1) At CB and valence band (VB) edges, the photogenerated electrons and holes undergo ns time scale recombination, meanwhile, the exciton energy of host transfer to Mn d-states and induce an exciton at Mn from 6 A 1 -4 T 1 (generally on the ps time scale). [43,53] 2) Charge recombination process of the Mn dopants from 4 T 1 -6 A 1 state, which displays ms scale lifetime and is a few orders magnitude longer than the host exciton. 3) Back transfer of electrons from the 4 T 1 state to the CB of the host.…”
Section: Pl Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…The photogenerated charge carriers in the Mn:CsPbCl 3 NCs have four elementary transfer routes: 1) At CB and valence band (VB) edges, the photogenerated electrons and holes undergo ns time scale recombination, meanwhile, the exciton energy of host transfer to Mn d-states and induce an exciton at Mn from 6 A 1 -4 T 1 (generally on the ps time scale). [43,53] 2) Charge recombination process of the Mn dopants from 4 T 1 -6 A 1 state, which displays ms scale lifetime and is a few orders magnitude longer than the host exciton. 3) Back transfer of electrons from the 4 T 1 state to the CB of the host.…”
Section: Pl Intensitymentioning
confidence: 99%
“…[ 32 ] This means that the originally short‐lived photogenerated charge carriers can be reserved at Mn 2+ dopants and exist for a significantly longer time. [ 43 ] Therefore, the reserved charge carriers at Mn 2+ dopants can in principle be readily extracted and utilized for surface reaction with less consumption by the fast charge recombination. [ 44 ] In addition, Kamat et al have reported that the midgap states created by Mn 2+ dopants can serve as the electron transfer mediator between CdS/CdSe and TiO 2 , [ 45 ] revealing that the charge carriers at Mn 2+ dopants can be extracted from the inside of the NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, there has been some problems and controversies about Mn 2+ emission, including the origin of the Mn emission, the energy level alignment, and the origin of the ns-scale lifetime component. Although many efforts and achievements have been made, there are still some difficulties. The energy/charge transfer processes from the host to Mn 2+ ions have attracted wide concern and enormous studies, while they are not completely known yet. …”
Section: Introductionmentioning
confidence: 99%
“…The CT mechanism dominates in Mn:CsPbCl 3 as a result of small energy barriers. 7 The surface-functionalized NCs of CsPbBr 3 are also reported to exhibit long-lived delayed luminescence. 8 The TET from the NCs to the phenanthrene ligands and the subsequent thermally activated reverse TET cause the emission from the CsPbBr 3 NCs to be delayed and long-lived.…”
mentioning
confidence: 99%
“…The enhanced dopant luminescence lifetime observed in Mn-doped lead halide perovskites (CsPbX 3 : X = Cl, Br, I) has been attributed to an interplay between the charge-transfer and energy-transfer mechanisms, depending on the energy barriers. The CT mechanism dominates in Mn:CsPbCl 3 as a result of small energy barriers . The surface-functionalized NCs of CsPbBr 3 are also reported to exhibit long-lived delayed luminescence …”
mentioning
confidence: 99%